2019
DOI: 10.15171/apb.2019.063
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional and Opposite Effects of Naïve Mesenchymal Stem Cells Ontumor Growth and Progression

Abstract: Cancer has long been considered as a heterogeneous population of uncontrolled proliferation of different transformed cell types. The recent findings concerning tumorigeneses have highlighted the fact that tumors can progress through tight relationships among tumor cells, cellular, and non-cellular components which are present within tumor tissues. In recent years, studies have shown that mesenchymal stem cells (MSCs) are essential components of non-tumor cells within the tumor tissues that can strongly affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 232 publications
0
13
0
Order By: Relevance
“…The TME, also known as the tumor stroma, consists of connective tissue and a variety of non-cancer cell types. Immune cells such as macrophages, cancer-associated fibroblasts (CAFs), and lymphocytes residing in the stroma have been shown to exhibit bidirectional effects on tumor progression (14)(15)(16). The tumor stroma is associated with prognosis in a variety of cancer types (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The TME, also known as the tumor stroma, consists of connective tissue and a variety of non-cancer cell types. Immune cells such as macrophages, cancer-associated fibroblasts (CAFs), and lymphocytes residing in the stroma have been shown to exhibit bidirectional effects on tumor progression (14)(15)(16). The tumor stroma is associated with prognosis in a variety of cancer types (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the potential benefits of using MSC as a cell delivery system, studies have reported the supportive role of MSC in the progression of tumor density and metastasis, while others have shown antitumor effects both in vitro and in different models of cancer ( Devarasetty et al, 2017 ; Liang et al, 2020 ; Xia et al, 2020 ). The conflicting data in the literature may hamper the establishment of cell therapies for cancer based on non-modified MSC since the therapeutic safety of such approach might be jeopardized ( Rahmatizadeh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the studies evaluating the effect of naïve MSC on tumor development employ MSC from the BM, the UCM, and the AT ( Rahmatizadeh et al, 2019 ; Liang et al, 2020 ; Xia et al, 2020 ). When analyzing the outcome from these studies, it seems to be a conspicuous pattern of tumorigenicity, with BM MSC being more pro-tumorigenic and UCM MSC being more tumor suppressive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of MSCs in tumors is still controversial, but their supportive role in tumor progression is dominant. 177,178 The results of two studies in EC also show that MSCs promote progression of tumor in vivo, 179,180 which is a promising therapeutic direction, but the research on its specific mechanism and related effects need to be further studied.…”
Section: Tumor Stromal Cells Are Imperative Supporters For Tmementioning
confidence: 99%